Drug-facilitated sexual assault and other crimes: A systematic review by countries. (April 2021) - García, M.G.; Pérez-Cárceles, M.D.; Osuna, E.; Legaz, I.
Abstract: Drug-facilitated sexual assault (DFSA) and drug-facilitated crime (DFC) constitute a mode of violence that is generally unknown to the population and may go unnoticed by health professionals. The aim of this systematic review was to analyze the victims of DFC, compiling their sociodemographic characteristics, the toxic substances used and their biological matrices and modes of action, in order to identify the substances that are commonly put to criminal use. The aim would be to establish political and health strategies that inform and warn people about possible criminal social behaviors consequent danger to health. This systematic review was conducted following the PRISMA guidelines. Alcohol, benzodiazepines and cocaine were among the most commonly detected substances. In most of the hospitals, immunoassays, liquid chromatography (LC-MS), or gas chromatography-mass spectrometry (GC-MS) analyses were used to identify the substances, while the most frequently used biological matrices were blood and urine. From a judicial point of view, the instrumental protocols and techniques followed for the detection of toxics in different biological matrices must guarantee the reliability and validity of the results for use in a court of law. The recommendations of international organizations should be followed and must be called upon to strengthen their respective national laws against this chemical submission (CS) phenomenon. Highlights: DFCs to differ between countries depending on recreational-drugs and social norms. The variability of substances makes their detection difficult in analytical tests. A global consensus on the DFCs protocol to be followed in all countries.